2020
DOI: 10.1101/2020.07.07.20148098
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Reversal of Epigenetic Age with Diet and Lifestyle in a Pilot Randomized Clinical Trial

Abstract: Manipulations to set back biological age and extend lifespan in animal models are well established, and translation to humans has begun. The length of human life makes it impractical to evaluate results by plotting mortality curves, so surrogate markers of age have been suggested and, at present, the best established surrogates are DNA methylation clocks. Herein we report on a randomized, controlled clinical trial designed to be a first step in evaluating the effect of a diet and lifestyle intervention on biol… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 51 publications
2
6
0
Order By: Relevance
“…In fact, we did not find any correlation between differences in LTL and in DNAmAge, and this result aligns with previous studies (Belsky et al, 2018;Marioni et al, 2018;Pavanello et al, 2019;Vyas et al, 2019). Despite the short time frame of our study, this timing choice was supported by our previous experience (Pavanello et al, 2019) and a thorough review of the existing literature (Figure 1), which showed that 6 of the 8 studies on positive effects on TL had a timeframe comprised between 1 and 3 months (Thimmapuram et al, 2017;Conklin et al, 2018;Innes et al, 2018;Tolahunase et al, 2018;Le Nguyen et al, 2019;Pavanello et al, 2019), while 2 out of the 4 studies on DNAmAge had a timeframe of 2 months (Pavanello et al, 2019;Fitzgerald et al, 2021). We therefore believe that this rationale provides a robust basis for the selected study.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In fact, we did not find any correlation between differences in LTL and in DNAmAge, and this result aligns with previous studies (Belsky et al, 2018;Marioni et al, 2018;Pavanello et al, 2019;Vyas et al, 2019). Despite the short time frame of our study, this timing choice was supported by our previous experience (Pavanello et al, 2019) and a thorough review of the existing literature (Figure 1), which showed that 6 of the 8 studies on positive effects on TL had a timeframe comprised between 1 and 3 months (Thimmapuram et al, 2017;Conklin et al, 2018;Innes et al, 2018;Tolahunase et al, 2018;Le Nguyen et al, 2019;Pavanello et al, 2019), while 2 out of the 4 studies on DNAmAge had a timeframe of 2 months (Pavanello et al, 2019;Fitzgerald et al, 2021). We therefore believe that this rationale provides a robust basis for the selected study.…”
Section: Discussionsupporting
confidence: 90%
“…Only one study considered art therapy (Mahendran et al, 2018). DNAmAge reduction was associated with improved lifestyle changes (Fitzgerald et al, 2021;Yaskolka Meir et al, 2021), diet (Gensous et al, 2020), and meditation and music listening (Pavanello et al, 2019). No study explored the effect of art therapy on DNAmAge.…”
Section: Introductionmentioning
confidence: 99%
“…methionine) restriction has been assessed as a means to reduce agedependent DNA methylation in healthy humans. 35,36 The current findings along with previously reported hypomethylation in SLE as compared to healthy controls and potential dietary effects on methylation 4,5,9,[11][12][13][14] thus suggest that DNA methylation is dependent upon diet irrespective of SLE disease status. The impact of dietary interventions on methylation status may differentially impact underlying diseases.…”
Section: Discussionsupporting
confidence: 66%
“…For instance, increased methylation may be desirable in SLE to reduce disease activity, while in healthy individuals, it may increase aging effects. 35,36 Thus, dietary counselling on an individual basis requires careful consideration of all these factors, as is best possible. Indeed, the majority of SLE patients actively seek self-empowerment and request counselling on dietary measures.…”
Section: Discussionmentioning
confidence: 99%
“…These criteria best facilitate the selection of a marker that measures the effectiveness of interventions on biological age reversal. Until recently, the possibility of biological age reversal was uncertain, but thanks to recent experimental trials utilizing biological age predictors we now know that biological age as measured by biomarkers of aging can be slowed or even reversed ( Fahy et al, 2019 ; Fitzgerald et al, 2020 ; Hachmo et al, 2020 ). With that in mind, our specific aim is to compile the available evidence related to various readily accessible biological age predictors.…”
Section: Introductionmentioning
confidence: 99%